Syphilis in pregnancy: Nurse’s roles - Onpiw, Nuttaya; NaoSrisorn, Panyupa; Sinthusiri, Payom (Journal of The Royal Thai Army Nurses, 2020)
At present, the trend of syphilis infection in pregnancy is increasing. Syphilis infection has impact on pregnant women fetus and newborns, husband and nation such as abortion, preterm labor, dead fetus in utero, congenital syphilis, transmission of the infection to husband and lost the budget for treatment etc. Therefore, midwives should give importance and have knowledge and understanding about the role of midwives in taking care of syphilis in pregnancy throughout the childbirth cycle including pregnancy, delivery and postpartum. To guide nursing care syphilis in pregnancy and screening for newborns with congenital syphilis. For reducing the impact and severity of syphilis on pregnancy fetuses and newborns, husbands and the nation.